Obesity impact on leukocyte telomere shortening and immune aging assessed by Mendelian randomization and transcriptomics analysis - Zhijun Feng; Jiacheng Li; Huimin Zhang; Shupeng Liu; Yinghui Wang; Meijuan Zhou; Zhenhua Ding; Lin Xiao (Scientific Reports)
Abstract Obesity and aging are key research topics in contemporary biomedical science. While studies have explored the effects of obesity on various health indicators, the precise mechanisms through which obesity may affect leukocyte telomere length (LTL)-and whether this impact contributes to accelerated immune cell senescence-remain unclear and warrant further investigation. In this study, we employed single nucleotide polymorphisms (SNPs) associated with four obesity indices—body mass index (BMI), body fat percentage (BFP), waist circumference (WC), and waist-hip ratio (WHR)—as instrumental variables (IVs) to assess the causal relationship between these indices and LTL through Mendelian randomization (MR) analysis. Additionally, we analyzed transcriptome sequencing data from peripheral blood mononuclear cells (PBMCs) across three groups: lean individuals, individuals with obesity before undergoing bariatric surgery, and individuals with obesity after surgery, and focus on the expression changes of cellular senescence and telomere dynamics related genes in PBMCs of individuals with obesity before and after weight loss intervention. The results showed a negative causal relationship between BMI (B=-0.04, P < 0.0001), BFP (B=-0.06, P < 0.0001) and LTL without being impacted by lipid profiles and T2D. The negative causal relationship between WC (B=-0.04, P < 0.0001) and LTL may be dependent on lipid levels, but not on T2D. WHR had no significant causal relationship (P > 0.05). Transcriptomic analysis further revealed that individuals with obesity had higher expression of cellular senescence-related genes such as ID2, LMNA, and TENT4B in PBMCs compared to lean individuals, with expression levels of these genes significantly decreasing after bariatric surgery. These findings underscore the detrimental impact of obesity on telomere attrition and immune cell senescence, highlighting the potential benefits of obesity management for slowing the biological process of cellular and immune aging.